Protecting the human rights of sexual minorities in contemporary Africa - Adrian Jjuuko (Pretoria University Law Press (PULP), 2017)
This collection of essays, Protecting the human rights of sexual minorities in contemporary Africa, contains papers that were first presented at a colloquium on sexual minority rights in Africa, which took place at the Centre for Human Rights, University of Pretoria, in December 2014. This event was made possible with the generous support of the Government of the Kingdom of Norway, through its Embassy in South Africa. These papers were subsequently peer-reviewed and reworked. Viewing homosexuality through a legal and rights-based prism, this volume brings together fourteen essays focusing on various aspects of homosexuality, covering a wide rage of countries from across the continent. The situation in nine countries (Botswana, Cameroon, Kenya, Mauritius, Mozambique, Nigeria, South Africa, Uganda and Zimbabwe) is reviewed; while other contributions are more regional in their perspective. This makes this publication one of the most comprehensive collections of African voices on this topic. For too long African voices have been silent on the fledgling discourse on sexual minorities. This volume seeks to amend this shortcoming. The editors and authors and contributors are not only African, but also, with a few exceptions, graduates of the Centre's Master's programme in Human Rights and Democratisation in Africa. The publisher is an African-based publisher, the Pretoria University Law Press (PULP), based at the Centre for Human Rights.